EXTRA-CURRICULAR ACTIVITIES AS AN EDUCATIONAL ALTERNATIVE FOR THE TRAINING OF TRANSVERSAL COMPETENCIES - Florentina MOGONEA (Universitaria Publishing House, Craiova, 2023)
The present study aims to address the importance of extracurricular activities in the training/ development of transversal competencies, approaching the issue in the context of the initial training of future teachers and from the perspective of this dimension of their competency profile. The approach we carried out presents this kind of activities as an alternative to the curricular ones, a complementary choice, intended to support the achievement of the educational goals. The research method used was a group interview, conducted with 12 students during the PsychoPedagogical Training Program, level II of advanced studies. The Extracurricular activitiesdrawn from the conversation with the 12 participants allowed the identification of some aspects regarding the implications of extracurricular activities in the formation of transversal competencies, regarding the methods of accomplishment, possible themes for reaching this type of activities.